The effects of type 2 diabetes mellitus on postural adaptation and complexity during a visual search task in older adults. - Manafi, Mahdiyeh M.; Wolfe, Alexander; Zhou, Junhong; Yu, Wanting; Iloputaife, Ikechukwu; You, Tongjian; Manor, Brad; Jor'dan, Azizah J. (Frontiers in Aging Neuroscience, 2025)
Background: Type 2 diabetes mellitus (T2DM) negatively impacts both the peripheral and central systems involved in postural control, leading to impairments, especially under dual-task conditions. This study investigated the effects of T2DM on postural sway using single- and multi-scale metrics during an attention-demanding dual-task standing protocol. Methods: Twenty-four relatively healthy older adults (76 ± 6 years) and 20 older adults with T2DM (76 ± 7 years) completed quiet standing (i.e., single-task, control) and dual-task (i.e., visual search) conditions. For the dual-task condition, participants counted the frequency of a designated letter in a block of text. Postural sway (i.e., elliptical area, jerk, path length, and range of acceleration) was assessed using a wearable motion sensor. Multi-scale entropy was used to quantify the complexity of postural sway in the medial-lateral (ML) and anterior-posterior (AP) directions. Postural adaptation was calculated as the percent change in sway metrics from control to visual search condition. Task performance was measured as percent accuracy in the visual search task. Results: Compared to the non-diabetic group, the T2DM group exhibited greater elliptical sway area (p = 0.007), jerk (p = 0.001), path length (p < 0.0001), and range of acceleration (p = 0.006), and lower ML sway complexity (p = 0.053), irrespective of task condition. There were no group differences in postural adaptation for any sway metric. Across participants, single-scale sway metrics were lower during the visual search compared to the control condition (p < 0.05). Within the non-diabetic group only, visual search performance was correlated with postural adaptation in elliptical sway area (r = −0.70, p < 0.0001) and range of acceleration (r = −0.66, p = 0.0009). Conclusion: The T2DM group exhibited altered single-scale sway measures and reduced ML sway complexity, highlighting the sensitivity of both single- and multi-scale postural sway metrics in detecting group differences in standing postural control. The link between postural adaptation and visual search performance, which was evident only in the non-diabetic group, may suggest a decoupling between perception and action in patients with T2DM.